A self-repairing super-hydrophobic protective packaging composite coating based on two-dimensional molybdenum sulfide and its preparation method and application
By applying a self-healing superhydrophobic protective coating based on two-dimensional molybdenum sulfide on tantalum capacitor devices, the stability of tantalum capacitors in high temperature and humidity environments is solved, achieving a longer service life and better electrical performance.
Patent Information
- Application Number
- CN202310310446.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-03-28
AI Technical Summary
Existing tantalum capacitor devices have poor stability in high temperature and humidity environments, resulting in short service life. The existing protection methods are mainly concentrated in the capacitor, affecting the capacitor's own performance.
Using a self-healing superhydrophobic protective encapsulation composite coating based on two-dimensional molybdenum sulfide, the self-healing superhydrophobic coating with ultraviolet light-responsive is modified by introducing amino acids or coupling agents to combine with organic silicone to form a self-healing superhydrophobic coating with ultraviolet light response. Enhance protection performance on the epoxy housing of the tantalum capacitor.
It significantly improves the protection performance and service life of tantalum capacitors, extends the durability of the coating, maintains good hydrophobicity, and shows more stable electrical properties in high temperature environments.
Smart Images

Figure CN116376431B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electronic device packaging, and specifically relates to a self-healing super-hydrophobic protective packaging composite coating based on two-dimensional molybdenum sulfide, and a preparation method and application thereof. The composite coating is especially used on tantalum capacitor devices commonly used in high-end fields such as military and aerospace. Background Art
[0002] Power electronics technology is becoming increasingly important in the fields of power generation, distribution and consumption. Since more than 70% of electricity is processed by power electronics, the reliability of power electronic products is very important. Among all electronic components, capacitors are the most vulnerable in terms of failure level and service life. Different types of capacitors are designed to meet different electrical, thermal and mechanical constraints associated with their use. Therefore, there are three different types of capacitors to meet all user needs: ceramic, film and electrolytic capacitors. Electrolytic capacitors have a high volumetric capacitance and are therefore widely used in the field of power electronics, mainly for filtering and energy storage. Tantalum capacitors, as a type of electrolytic capacitor, are more expensive per unit price. Their advantages are small size, large capacity, stable electrical performance and high reliability. They have a stable market share and performance advantages in the field of high-end capacitors, and have better stability, wider operating temperature range and longer service life than other capacitors. The anode of solid tantalum capacitors is sintered by tantalum powder and led by tantalum wire. Ta2O5 is used as the dielectric layer. The cathode is PEDOT polymer or MnO2, and is bonded to the negative electrode through graphite and silver paste. Finally, the epoxy shell is molded to protect the internal structure of the capacitor.
[0003] Although tantalum capacitors are encapsulated with epoxy shells, water vapor will still invade the inside of the device, resulting in reduced stability of tantalum capacitors. Based on the protection of tantalum capacitors, people usually start from the internal structure of the capacitor. Residual ions in the PEDOT:PSS electrode will lead to the accumulation of dielectric-cathode interface charge. Therefore, after each dispersion and impregnation step, an additional water washing process is required to improve the stability of the capacitor; the ESR value and capacitance frequency performance of the PEDOT:PSS electrode treated with ethylene glycol are significantly improved, and the leakage current of the capacitor is also significantly reduced; coating a moisture protection layer on the annealed PEDOT:PSS electrode is also an effective protection method. The capacitor coated with a moisture protection layer has a certain improvement in moisture resistance and solvent resistance. The effects of different dielectric thicknesses on tantalum capacitors vary greatly. Capacitors with thicker dielectric films are usually more stable than capacitors with thinner dielectric films. The high temperature characteristics of tantalum capacitors are also a bottleneck that limits the widespread application of capacitors. At present, the temperature limit of 105°C is generally adopted internationally. Through shielding and pretreatment of dielectrics, processing of organic solid dielectrics, and improvements in packaging layers, the temperature limit of tantalum capacitors can be increased to 125°C.
[0004] All of the above protection methods have achieved good results, but these methods are all applied inside the capacitor, so the impact on the capacitor itself also needs to be carefully considered. However, re-packaging the epoxy shell can avoid this effect. Inspired by the super-hydrophobic phenomenon of lotus leaves, we applied super-hydrophobic coatings to the field of tantalum capacitor packaging, but the durability of super-hydrophobic coatings is a practical issue that people are very concerned about. In recent years, self-healing materials have attracted more and more attention. When the material is damaged, it can autonomously repair physical damage under external stimuli such as heat, light and solvents. In order to meet the needs of super-hydrophobic materials for use in different environments and extend their service life, combining self-healing function with super-hydrophobic surface will significantly increase the service life of the coating. Therefore, we designed and prepared a self-healing hydrophobic coating based on tantalum capacitor packaging, and applied the hydrophobic coating with self-healing function to the surface of the epoxy shell.
[0005] At the same time, we also noticed that two-dimensional MoS2 has attracted much attention from scientific researchers because of its outstanding electronic, optical and mechanical properties. The polarity of the edge and plane of MoS2 nanosheets is different, the edge is hydrophilic and the plane is hydrophobic. Based on the original self-healing coating, we introduced modified MoS2 with amino acids modified at the edge, and designed and prepared self-healing super-hydrophobic modified MoS2 packaging materials. Summary of the invention
[0006] In order to overcome the deficiencies and shortcomings of the prior art, the primary purpose of the present invention is to provide a method for preparing a self-repairing super-hydrophobic protective packaging composite coating based on two-dimensional molybdenum sulfide, wherein the composite coating preparation method uses an organic silica gel modified with two-dimensional flaky molybdenum sulfide introduced with amino acids or coupling agents as a substrate, and a titanium dioxide super-hydrophobic coating with ultraviolet light response as a surface layer, thereby forming a self-repairing super-hydrophobic protective packaging composite coating with ultraviolet light response. Thus, we propose an efficient tantalum capacitor packaging method: the modified two-dimensional flaky molybdenum disulfide is introduced, and its special structural properties can effectively block water vapor, thereby further improving the protective performance of the coating.
[0007] The second purpose of the present invention is to provide a self-healing super-hydrophobic protective packaging composite coating based on two-dimensional molybdenum sulfide prepared by the above-mentioned preparation method. The water contact angle of the composite coating is less than or equal to 120°. When irradiated with ultraviolet light for seconds, the organic silica gel can be decomposed into small molecules with low surface energy and diffused to the surface of the coating, thereby reducing the surface energy of the surface layer and performing self-repair.
[0008] The third object of the present invention is to provide the application of the above-mentioned self-repairing super-hydrophobic protective packaging composite coating based on two-dimensional molybdenum sulfide.
[0009] The primary purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a self-repairing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide comprises the following steps:
[0011] (1) Preparation of superphobic aqueous solution: dissolving titanium dioxide in an organic solvent containing perfluorosilane to obtain a superphobic aqueous solution;
[0012] (2) Preparation of modified molybdenum disulfide (MoS2): prepare an amino acid or coupling agent aqueous solution, stir magnetically, vacuum filter the solution, and dry the precipitate to obtain modified molybdenum disulfide (MoS2);
[0013] (3) Preparation of an organosilicon solution containing modified molybdenum disulfide (MoS2): mixing the modified molybdenum disulfide (MoS2) prepared in step (2) with organic silica gel, and stirring at room temperature to obtain an organosilicon solution containing modified molybdenum disulfide (MoS2);
[0014] (4) The organosilicon solution containing modified molybdenum disulfide in step (3) is evenly sprayed on the surface to be sprayed, heated and formed, and then the super-hydrophobic solution in step (1) is evenly sprayed, and placed at room temperature. After the organic solvent evaporates, a self-healing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide is prepared.
[0015] Preferably, in step (1), the mass ratio of titanium dioxide to organic solvent is (1-5):100; the mass ratio of perfluorosilane to organic solvent is (1-10):100.
[0016] Preferably, the titanium dioxide in step (1) is anatase; the perfluorosilane is any one of 1H, 1H, 2H, 2H perfluorooctyltrimethoxysilane, 1H, 1H, 2H, 2H perfluorooctyltriethoxysilane, and 1H, 1H, 2H, 2H perfluorododecyltrimethoxysilane; and the organic solvent is any one of ethanol, acetone, ethyl acetate, and butyl acetate.
[0017] Preferably, the amino acid in step (2) is any one of aspartic acid, lysine, alanine, tryptophan, proline and glutamic acid; or, the coupling agent is any one of KH550, KH540, KH792 and KH602.
[0018] Preferably, in step (2), the drying temperature is 60-100° C. and the drying time is 6-12 h.
[0019] Preferably, the added mass of the modified molybdenum disulfide (MoS2) in step (3) is 0.5% to 2% of the organic silica gel.
[0020] Preferably, the organic silica gel in step (3) is a polysiloxane with a silicon-oxygen bond (-Si-O-Si-) as a skeleton.
[0021] Preferably, the heating temperature in step (4) is 50-100° C., and the heating time is 1-6 hours.
[0022] The second object of the present invention is achieved by the following technical solutions:
[0023] A self-repairing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide is prepared by the above preparation method.
[0024] The third object of the present invention is achieved by the following technical solutions:
[0025] A self-healing superhydrophobic protective packaging coating based on two-dimensional molybdenum sulfide and its application in tantalum capacitors.
[0026] Specifically, the two-dimensional molybdenum sulfide-based self-healing super-hydrophobic protective packaging coating is applied to the surface of the epoxy shell of the tantalum capacitor.
[0027] The advantages and beneficial effects of the present invention over the prior art are as follows:
[0028] (1) Compared with the currently commonly used epoxy shell packaging method for electronic devices, the present invention is the first to use a self-healing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide to achieve external packaging of the epoxy shell, which has not been reported in previous literature and patents. The modified titanium dioxide surface layer and organic silica gel have excellent hydrophobicity. Therefore, the self-healing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide is used in tantalum capacitors. The protective sealing performance is very good.
[0029] (2) When the surface energy of the self-healing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide prepared by the present invention increases after a certain period of time or when it is damaged, the surface layer is irradiated with ultraviolet light. Due to the photoresponse of titanium dioxide, the organic silica gel in the bottom layer is decomposed into small molecules with low surface energy and diffused to the surface layer, thereby reducing the surface energy of the coating and maintaining its good hydrophobic protective properties.
[0030] (3) The self-healing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide described in the present invention is prepared by adding flaky two-dimensional molybdenum disulfide. Since flaky two-dimensional molybdenum disulfide has the characteristics of being hydrophobic in the middle and hydrophilic at the edge, we modify the molybdenum disulfide with amino acids to change its edge characteristics from hydrophilic to hydrophobic. The modified molybdenum disulfide is added to organic silica gel. Due to the special two-dimensional flaky structure of molybdenum disulfide, the path of water vapor invasion can be greatly extended, thereby further improving the hydrophobic protective property of the coating.
[0031] (4) The present invention pioneered the use of a self-healing super-hydrophobic method to encapsulate tantalum capacitors, which achieved innovation in principle and had little impact on the internal structure of the tantalum capacitor, significantly improving the yield rate. According to aging test results, the self-healing super-hydrophobic protective packaging coating of the present invention can extend the service life of the tantalum capacitor to more than 12 years. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of a tantalum capacitor encapsulated with a self-repairing super-hydrophobic protective encapsulation coating based on two-dimensional molybdenum sulfide prepared by the present invention;
[0033] Figure 2 The effect of the amount of perfluorosilane added in Example 2 on the wettability of the self-healing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide;
[0034] Figure 3 The water contact angle diagrams of the blank group, organic silica gel group and PVA group under different illumination times in Example 3;
[0035] Figure 4 (a) and Figure 4 (b) is the SEM image of molybdenum disulfide. Figure 4 (c) is the SEM image of modified molybdenum disulfide organic silica gel. Figure 4 (d) is the SEM image of molybdenum disulfide organic silica gel;
[0036] Figure 5 The surface morphologies of the coatings of the blank group, the organic silica gel group and the PVA group before and after illumination described in Example 5, wherein Figure 5 (a) is the SEM image of the blank group before illumination. Figure 5 (b) is the SEM image of the blank group after illumination. Figure 5 (c) is the SEM image of the organic silica gel group before illumination. Figure 5 (d) is the SEM image of the organic silica gel group after illumination. Figure 5 (e) is the SEM image of the PVA group before illumination. Figure 5 (f) is the SEM image of the PVA group after illumination;
[0037] Figure 6 FTIR spectra analysis of the surface coatings of the blank group, the organic silica gel group and the PVA group before and after illumination described in Example 6;
[0038] Figure 7 These are the accelerated test parameters of the blank group, organic silica gel group and PVA group of tantalum capacitors described in Example 7 (before light irradiation);
[0039] Figure 8 These are the accelerated test parameters (after light exposure) of the blank group, organic silica gel group and PVA group of tantalum capacitors described in Example 8;
[0040] Fig. 9 FTIR spectra of alanine, lysine and aspartic acid modified molybdenum disulfide described in Example 9;
[0041] Fig.10The Raman spectra of molybdenum disulfide modified with alanine, lysine and aspartic acid described in Example 10;
[0042] Fig.11 This is the effect of the amount of modified molybdenum disulfide added as described in Example 11 on the protection performance of tantalum capacitors. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0044] Example 1
[0045] Titanium dioxide powder was dissolved in an organic solvent of 1H, 1H, 2H, 2H perfluorooctyl triethoxysilane to obtain a superphobic aqueous solution, wherein the ratio of 1H, 1H, 2H, 2H perfluorooctyl triethoxysilane to the organic solvent was 1:100, 2mmol amino acids (lysine, aspartic acid, alanine) and 12.5mmol MoS2 were added to 100ml deionized water and stirred in a magnetic stirrer for 12 hours. The solution was filtered by vacuum filtration, and the black precipitate was dried at 60°C for 12 hours. Then, three amino acid-modified MoS2 were obtained. 0.05, 0.1, 0.15, and 0.2 g of amino acid-modified molybdenum disulfide (two-dimensional flakes) were respectively added to a beaker containing 10 g of organic silica gel, and stirred at room temperature for 1 hour to obtain organic silica gel solutions containing modified molybdenum disulfide in different proportions. 2 mL of the organic silica gel solution containing modified molybdenum disulfide was evenly sprayed on the epoxy shell of the tantalum capacitor and heated at 50°C for 10 hours. After the organic silica gel was heated and formed, 2 mL of the superhydrophobic solution was evenly sprayed on its surface, and then placed at room temperature for 24 hours to allow the organic solvent to completely evaporate before completing the encapsulation. A tantalum capacitor containing a self-healing superhydrophobic protective encapsulation coating based on two-dimensional molybdenum sulfide was prepared.
[0046] Example 2
[0047] In order to explore the effect of the amount of perfluorosilane added on the wettability of the super-hydrophobic coating, a comparative experiment with different ratios was set up. Figure 2 It can be seen that when M _二氧化钛 :M _全氟硅烷 When the ratio of fluorosilane to titanium dioxide is 1:3, the wettability of the prepared self-healing superhydrophobic protective packaging coating based on two-dimensional molybdenum sulfide is optimal. The coating performance can be maximized by modifying titanium dioxide with an appropriate amount of perfluorosilane. If too little fluorosilane is used for modification, the surface energy of the surface layer is low and is not enough to achieve superhydrophobicity. If too much fluorosilane is used for modification, the organic solvent will not be fully dissolved, thereby reducing the hydrophobicity of the coating.
[0048] Example 3
[0049] For the convenience of testing and characterization, all experimental coatings were applied on glass substrates, and ultraviolet light irradiation was used to simulate the loss of coatings. In order to compare the performance with the silicone substrate, a blank group and a PVA group were set up in the experiment. The silicone group and the PVA group embedded the silicone coating and the PVA coating between the substrate and the titanium dioxide coating, while the blank group directly sprayed the super-hydrophobic coating on the epoxy shell of the tantalum capacitor.
[0050] Depend on Figure 3 It can be seen that the titanium dioxide coating modified by 1H, 1H, 2H, 2H perfluorooctyl triethoxysilane has good superhydrophobic properties, and its initial water contact angle is 161.3°. Under ultraviolet light irradiation, the titanium dioxide valence band electrons are excited to the conduction band, and the electrons and holes migrate to the surface, generating electron-hole pairs on the surface. The electrons react with titanium, and the holes react with the surface bridge oxygen ions to form positive trivalent titanium ions and oxygen vacancies, respectively. At this time, the water in the air dissociates and adsorbs in the oxygen vacancies to become chemically adsorbed water, which can further adsorb moisture in the air to form a physical adsorption layer. With the increase of illumination time, the hydrophobicity of the surface coating decreases. It can be seen that after 120s of ultraviolet light irradiation, the hydrophobicity of the blank group and the PVA group has disappeared, but the water contact angle of the organic silica gel group is still maintained at about 160°, indicating that the organic silica gel group still has good protective hydrophobicity after being damaged.
[0051] Example 4
[0052] Figure 4 (a) and Figure 4 (b) Mo synthesized by hydrothermal method S2 SEM image. Through SEM, it can be observed that the synthesized MoS2 is a nanosphere composed of many nanosheets. This unique structure can be used for capacitor outer coating protection. The stacked nanosheets can extend the path of water vapor intrusion to a limited extent, thereby extending the service life of the device.
[0053] MoS2 is easy to agglomerate due to the Van der Waals force and is not easy to disperse in the resin matrix, which limits the wide application of MoS2 in composite materials. MoS2 covalently modified with KH550 produces more active sites on the surface of the nanosheets, thereby increasing its dispersibility with the matrix. The dispersibility of functionalized MoS2 in silicone is much better than that of MoS2 in silicone. Figure 4 (c) and Figure 4 (d) also shows that the modified molybdenum disulfide can be evenly dispersed in the silicone matrix.
[0054] Example 5
[0055] like Figure 5 (a)~ Figure 5(f) shows the surface morphology of the coatings in the blank group, silicone group and PVA group before and after illumination. It can be seen that before UV irradiation, the coating is mainly composed of large particles formed by the agglomeration of TiO2, forming a large number of air holes, resulting in a rough surface. After UV irradiation, the surface morphology of the blank group and the PVA group did not change much, indicating that the surface morphology of the composite structure has a relatively weak effect on the change of wettability. The surface of the silicone group has air holes filled with small molecules that diffuse upward to varying degrees, and the surface becomes dense, but its surface is still rough. We speculate that these small molecules that diffuse upward are low surface energy small molecules decomposed from silicone.
[0056] Example 6
[0057] In order to confirm the composition of these upwardly diffusing small molecules in Example 5, we performed Fourier transform infrared spectroscopy (FTIP). Figure 6 The following are the spectra of the surface coatings of the blank group, silicone group, and PVA group before and after illumination. After 120 seconds of illumination, the wettability of the coating surface of the blank group changed from hydrophobic to hydrophilic, with a peak at 1238 cm -1 、1200cm -1 、1147cm -1 It represents the stretching vibration peak of the carbon-fluorine bond. From the figure, it can be seen that the stretching vibration peak intensity of the carbon-fluorine bond is greatly reduced after light exposure. The organic silica group can be detected at 2962cm on the surface after light exposure. -1 、1256cm -1 、1064cm -1 and 1014cm -1 These three represent silicone CH, CH _3 The characteristic peaks of Si-O and CH4 confirm that the small molecules diffusing upwards belong to silicone. When the coating is damaged and the surface energy increases, the small molecules diffusing upwards can reduce the surface energy in time, thereby better maintaining the hydrophobicity of the coating. _2 There is a slight blue shift, which is caused by the interaction between the small molecules decomposed by silicone and the surface TiO2. The interaction between them is just physical filling, and no chemical reaction occurs. -1 、1639cm -1 It is the hydroxyl vibration peak of PVA. No hydroxyl vibration peak was detected after illumination, indicating that the PVA with the composite structure cannot diffuse to the surface.
[0058] Example 7
[0059] Tantalum capacitors have four important parameters, namely leakage current, capacitance, dissipation factor and ESR value. When the device performance degrades or fails, the rate of change of device parameters will increase accordingly. Figure 7The figure shows the change rate of the four parameters of the tantalum capacitor after the "double 85" test, among which the leakage current is a parameter that people pay more attention to. It can be seen from the figure that the blank group, the blank group and the PVA group are not as good as the silicone group in terms of device protection performance. Secondly, because PVA is hydrophilic, before 764h, when the water it absorbs has not reached saturation, the environment faced by the device is not as bad as the blank group. When it is saturated with water, the impact on the device parameters is greater than that of the blank group. There is not much difference between the three experimental groups in terms of the capacitance change rate. The change rate of the device's loss factor and the change rate of the ESR value are also similar to the leakage current change rate. The silicone group is better than the blank group and the PVA group in protecting the device. When the PVA group is saturated with water, the impact on the device parameters is greater than that of the blank group.
[0060] Example 8
[0061] like Figure 8 As shown in the figure, after exposure to light, silicone will be decomposed into small molecules with low surface energy and diffuse to the surface layer, thus preventing the surface layer from being further damaged. After 1004 hours of accelerated testing, in terms of the change rate of leakage current, the protection performance of the silicone group is still twice that of the blank group. The change rate of loss factor and ESR value is smaller than that of the device parameters before exposure to light, indicating that the protection performance of the coating on the device is increased after exposure to light.
[0062] Example 9
[0063] MoS2 modified with alanine, lysine and aspartic acid are called Ala-MoS2, Lys-MoS2 and Asp-MoS2 respectively. Fig. 9 The FTIR spectra of the original MoS2 sample and the modified MoS2 sample are shown in the figure. It can be seen from the spectra that the peak of molybdenum-sulfur bond (467cm -1) The amino group (1610 cm -1 ), proving that the three amino acids were successfully grafted onto MoS _2 superior.
[0064] Example 10
[0065] like Fig.10 As shown in the figure, we modified MoS with alanine, lysine, and aspartic acid. _2 Raman spectroscopy was performed to characterize the three amino acid-imprinted MoS _2 ,A 1g Mode stays at 402cm -1 and Mode shift to 373cm -1 , which may be the polar attraction between amino acids and the edge of MoS2.
[0066] Embodiment 11
[0067] We introduced functionalized flake molybdenum disulfide modified by amino acids at the edge of the original self-healing coating to prepare a self-healing hydrophobic coating based on tantalum capacitor encapsulation, thereby effectively improving the hydrophobicity and mechanical properties of the coating. We set different proportions of addition, Fig.11 It can be seen that the performance is best when the modified molybdenum disulfide addition is 1.5%. After 1004h of accelerated testing, the leakage current change rate of the tantalum capacitor is as low as 75.9%, which is two-thirds higher than the protection performance without the addition of modified molybdenum disulfide. The ESR value change rate of the tantalum capacitor is as low as 14.7%, which is twice as high as the protection performance without the addition of modified molybdenum disulfide. This shows that the addition of modified molybdenum disulfide improves the overall performance of the self-healing coating system.
[0068] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. Application of a self-repairing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide in tantalum capacitors, characterized in that: The method for preparing the self-repairing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide comprises the following steps: (1) Preparation of superphobic aqueous solution: dissolving titanium dioxide in an organic solvent containing perfluorosilane to obtain a superphobic aqueous solution; (2) Preparation of modified molybdenum disulfide: preparing an amino acid or coupling agent aqueous solution, magnetically stirring, vacuum filtering the solution, and drying the precipitate to obtain modified molybdenum disulfide; (3) Preparation of an organosilicon solution containing modified molybdenum disulfide: mixing the modified molybdenum disulfide prepared in step (2) with organic silica gel, and stirring at room temperature to obtain an organosilicon solution containing modified molybdenum disulfide; (4) uniformly spraying the organosilicon solution containing modified molybdenum disulfide in step (3) on the surface to be sprayed, heating and forming, and then uniformly spraying the super-hydrophobic solution in step (1), leaving it at room temperature, and after the organic solvent evaporates, preparing a self-repairing super-hydrophobic protective encapsulation coating based on two-dimensional molybdenum sulfide; In step (1), the mass ratio of titanium dioxide to organic solvent is (1-5):100; the mass ratio of perfluorosilane to organic solvent is (1-10):100; In step (1), the titanium dioxide is anatase; the perfluorosilane is any one of 1H, 1H, 2H, 2H perfluorooctyltrimethoxysilane, 1H, 1H, 2H, 2H perfluorooctyltriethoxysilane, and 1H, 1H, 2H, 2H perfluorododecyltrimethoxysilane; and the organic solvent is any one of ethanol, acetone, ethyl acetate, and butyl acetate; The added mass of the modified molybdenum disulfide in step (3) is 0.5% to 2% of the organic silica gel.
2. The application of the self-repairing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide in tantalum capacitors according to claim 1 is characterized in that: In step (2), the amino acid is any one of aspartic acid, lysine, alanine, tryptophan, proline, and glutamic acid; or, the coupling agent is any one of KH550, KH540, KH792, and KH602.
3. The application of the self-repairing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide in tantalum capacitors according to claim 1, characterized in that: In step (2), the drying temperature is 60°C-100°C and the drying time is 6-12h.
4. The application of the self-repairing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide in tantalum capacitors according to claim 1, characterized in that: The organic silica gel in step (3) is a polysiloxane with a silicon-oxygen bond as a skeleton.
5. The application of the self-repairing super-hydrophobic protective packaging coating based on two-dimensional molybdenum sulfide in tantalum capacitors according to claim 1, characterized in that: The heating temperature in step (4) is 50-100° C. and the heating time is 1-6 h.
Citation Information
Patent Citations
TiO2 acrylic resin super-hydrophobic coating and preparation method thereof
CN109233372A
Special anticorrosive damp-heat-resistant coating for tantalum capacitor as well as preparation method and application of special anticorrosive damp-heat-resistant coating
CN114539872A
KR20210157187A